2014
DOI: 10.1021/sb400206c
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Characterizing the Fast Dynamics of RNA Genetic Circuitry with Cell-Free Transcription–Translation (TX-TL) Systems

Abstract: RNA regulators are emerging as powerful tools to engineer synthetic genetic networks or rewire existing ones. A potential strength of RNA networks is that they may be able to propagate signals on time scales that are set by the fast degradation rates of RNAs. However, a current bottleneck to verifying this potential is the slow design-build-test cycle of evaluating these networks in vivo. Here, we adapt an Escherichia coli-based cell-free transcription-translation (TX-TL) system for rapidly prototyping RNA net… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(205 citation statements)
references
References 49 publications
8
197
0
Order By: Relevance
“…The data presented also provide evidence for the mechanism and importance of interior loops within antisensemediated transcriptional regulatory systems, which are being shown to be increasingly important for synthetic biology applications Chappell et al 2015a;Takahashi et al 2015). Initial in vitro structural analysis of In-cell SHAPE-Seq reactivity spectra for the upper portion of NP Fusion 1 and 2 hairpin stems.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The data presented also provide evidence for the mechanism and importance of interior loops within antisensemediated transcriptional regulatory systems, which are being shown to be increasingly important for synthetic biology applications Chappell et al 2015a;Takahashi et al 2015). Initial in vitro structural analysis of In-cell SHAPE-Seq reactivity spectra for the upper portion of NP Fusion 1 and 2 hairpin stems.…”
Section: Discussionmentioning
confidence: 85%
“…1A; Novick et al 1989;Brantl and Wagner 2000). Because they regulate downstream RNA synthesis as a function of an RNA input, attenuators can also be used in synthetic, RNA-only transcription networks that propagate signals directly as RNA molecules Takahashi et al 2015). Attenuators also have the potential to simplify the construction of genetic networks by removing the need to express intermediate protein species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, commercially available cell-free transcription/translation systems (bacterial or mammalian) are freeze-dried onto paper or other porous substrates to create poised genetic regulatory networks that are stable for long-term storage at room temperature and are activated by rehydration. This work follows on other efforts in cell-free synthetic biology, which have provided important dynamic and mechanistic insight on gene regulatory networks and allowed for rapid "build-test" cycles for prototyping engineered gene circuits and biomanufacturing pathways (36)(37)(38)(39)(40)(41). The in vitro nature of these systems resolves the challenge faced by cell-based approaches of importing biomolecular components into the intracellular space, making these cell-free environments easily modified and excellent platforms for engineering.…”
Section: In Vitro Diagnosticsmentioning
confidence: 99%
“…These regulators are special because they can be wired together into RNA-only genetic circuits that propagate information as RNAs without the need to translate or degrade intermediate regulatory proteins 12 . Recently it has been shown that RNA transcriptional repressors, also known as attenuators 13 can be configured into NOR logic gates and transcriptional cascades 12 . They can also be used to construct more sophisticated circuits, such as single-input modules 14 that sequentially activate the expression of multiple target genes 15 . Advances in RNA engineering approaches have also greatly expanded the types of circuits that can be built out of RNA mechanisms.…”
Section: Introductionmentioning
confidence: 99%